ANALISIS FAKTOR YANG MEMPENGARUHI PRODUKSI PADA PABRIK PENGOLAHAN KELAPA SAWIT DI PT. PERKEBUNAN NUSANTARA III KEBUN AEK TOROP,SUMATERA UTARA - Maurien E Situmeang; Azwar Harahap; Any Widayatsari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This research was conducted in PT. Perkebunan Nusantara III Kebun Aek Torop, North Sumatra. This research aims to know the factors that affect the production of palm oil processing plant at PT. Perkebunan Nusantara III Kebun Aek Torop, North Sumatra. In this data that become the population and sample the entire object reports annually from PT. Perkebunan Nusantara III Kebun Aek Torop. This research data using time series data consisting of 10 years starting from the year of 2005-2015. Sampling technique is used is to do an observation that is by collecting data and observe directly the object of research from data obtained in the Office of the factory oil palm PT. Perkebunan Nusantara III Kebun Aek Torop. Types of data used in this research is secondary data. Methods of analysis used in this research is quantitative descriptive method, analysis of partially and simultaneous (multiple linear regression analysis with the help of the program SPSS version 21.0). From the results of research that has been conducted, simultaneous regression test (F Test) shows that the whole of the free variables examined have significant influence towards the production of palm oil. Partial regression test (test t) indicates that the variable raw materials have positive and significant influence against the variable production of palm oil. While labor and capital has a negative influence and not significantly to the production of palm oil. And the most dominant variable against oil palm production in plantations of PT. Perkebunan Nusantara III Kebun Aek Torop raw materials. The magnitude of the influence brought about by a third (R2 ) these variables together against the variable terikatnya 94.8%, while the rest amounted to 5.2% is affected by other variables not examined in this study.Keywords: Production, Labour, Capital, Raw Materials and Oil Palm.